Fluoropolymer impregnated graphite foil as a bipolar plates of vanadium flow battery. (27th July 2021) - Loktionov, Pavel; Kartashova, Natalia; Konev, Dmitry; Abunaeva, Lilia; Antipov, Anatoly; Ruban, Eugeny; Terent'ev, Alexander; Gvozdik, Natalia; Lyange, Maria; Usenko, Andrey; Stevenson, Keith
Summary: Renewable energy in recent years plays an increasingly important role in the energy industry. Therefore, the problem of inventing efficient and affordable energy storage devices is of current importance. Vanadium redox flow battery stands out between a wide range of various chemical sources of electric energy. Discovering the way for optimizing the price of energy storage is one of the most important questions of the mentioned battery. New graphite‐polymer composite materials study shows that they may become a replacement for commonly used brittle graphite. The current article presents the study of graphite foil (or flexible graphite) filling with a copolymer of tetrafluoroethylene and vinylidene fluoride F‐42 properties. The article uses an implementation approach of putting the fluoropolymer into the pores of graphite foil, which shows a slight decrease in electrical conductivity, while a significant increase in its electrochemical stability in comparison with untreated graphite foil. Testing results of such material as current collectors (or bipolar plates) in a single membrane‐electrode assembly of vanadium redox flow battery cell show peak value of discharge power density of 843 mW/cm 2, energy efficiency of 78%‐79% during cycling at 200 mA/cm 2 allowing us to assume the possibility of its successful application in redox flow battery stacks.